Contribution of the Russian Federation to strengthening of epidemiological surveillance Over Dangerous Infectious Diseases in the Republic of Guinea - A. Yu. Popova; V. Yu. Smolensky; Yu. V. Demina; V. V. Maleev; V. V. Kutyrev; S. A. Shcherbakova; R. A. Maksyutov; O. V. Pyankov; S. Keita; M. Y. Buaro; N. Magassouba; Y. Yu. Itskov; et al. (Проблемы особо опасных инфекций, 2019)
The review summarizes the main results of a five-year cooperation activities of the specialists from the Russian Federation and the Republic of Guinea in the fight against dangerous infectious diseases. From the very beginning of the Ebola virus disease epidemic in West Africa, Russia has been actively involved in international efforts to control it. The scientific and technical interaction of the Russian Federation and the Republic of Guinea, the main components of which are strengthening of the laboratory and hospital facilities, training of specialists, can be divided into two stages. The first one (during the period of the epidemic) is sending to Guinea a group of Russian specialists and mobile laboratories from the mobile complex of the specialized anti-epidemic team of the Rospotrebnadzor and opening of the first in the Republic of Guinea inpatient infectious disease hospital for Ebola patients. The second one (after the end of the epidemic) is the creation of a high-tech Center, which allows performing both diagnostic and scientific researches of a wide range. In the course of implementation of the programs on assistance to the Republic of Guinea on combating infectious diseases, public-private partnership mechanisms with UC RUSAL were involved, which made it possible for Russia to participate in the eradication of the Ebola epidemic and the subsequent strengthening of Guinea’s national potential in combating biological threats as efficiently as possible. The five-year interaction between the Russian Federation and the Republic of Guinea resulted in the build-up of Guinea’s national potential to counter biological threats, the creation of laboratory and hospital resources that meet the needs for the elimination of epidemiological threats caused by particularly dangerous infectious diseases, not only in the Republic of Guinea, but also in neighboring countries of West Africa, development of scientific and technical cooperation aimed at improving the system of epidemiological surveillance of communicable diseases in the Republic of Guinea.